Planning Data Based Report on Education - Andi Suhandi; Faishal Hakim Qudus; Apriantono (PT. Lancar Media Komunikasi, 2023)
The results of the education evaluation received every year by the previous school were in the form of Education Quality Report Cards, which then changed to become Education Report Cards effective from 2021 in line with the changes to the independent curriculum and the elimination of the National Examination and the implementation of a national assessment in each educational unit. The Education Report Card provides report data on the results of the evaluation of the education system which places more emphasis on the quality of education and an integrated system, that is, the evaluation that is carried out no longer highlights students or equal access to education, but is more oriented towards the quality of education services, and integrates all data sourced from various applications that used and analyzed then entered into one application, namely the Education Report Card application